PENGARUH CORPORATE SOCIAL RESPONSIBILITY, AUDITOR OPINION, FINANCIAL DISTRESS DAN ACCOUNTING FIRM SIZE TERHADAP AUDITOR SWITCHING - Agus Setiawan, I Made; Aryani M., Ni Ketut Lely (E-Jurnal Akuntansi; Vol 8 No 2 (2014), 2014)
Auditor independence is an issue that causes the change of auditors (auditor switching) or Public Accounting Firm. One suggestion that auditors remain objective in carrying out auditing tasks is the mandatory rotation of auditors. Rotation of auditors is associated with the company's actions to make the turn auditor (auditor switching) or Public Accounting Firm. The purpose of this study was to determine the effect of corporate social responsibility, the auditor's opinion, financial distress and accounting firm size on auditor switching. This study uses data on real estate and property companies listed in Indonesia Stock Exchange 2008-2012 period. The samples in this study using purposive sampling method, the number of observations of a sample of 90 studies. The technique of data analysis is logistic regression analysis, because the dependent variable using dummy variable. Based on the results of analysis show that the variables of corporate social responsibility, the auditor's opinion and financial distress does not significantly influence the auditor switching. While accounting firm size variable is negative and significant effect on switching auditors.
Keywords: Auditor Switching, Corporate Social Responsibility, Auditor Opinion, Financial Distress, Accounting Firm Size